2008
DOI: 10.1111/j.1467-8489.2007.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotational grazing adoption in cattle production under a cost‐share agreement: does uncertainty have a role in conservation technology adoption?

Abstract: Rotational grazing has been promoted as a best management practice with environmental benefits and associated higher revenue. Its adoption rate has been relatively low. This study investigates the role of uncertainty in the adoption of rotational grazing with a cost-share by cattle producers. Mail survey results indicate that 63-71 per cent of cattle producers are uncertain about adoption with a government cost-share. The study suggests that the possibility of uncertainty should be considered in cases where wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…In line with other studies (Davies and Hodge 2006;Bewsell et al 2007;Kim et al 2008) the landholder survey was found to be a useful tool for identifying the attitudes, impediments and drivers of management adoption amongst landholders (Bewsell et al 2007). In this case, the survey provided an understanding of the broad impediments to and perceived benefits of adoption of water quality management.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In line with other studies (Davies and Hodge 2006;Bewsell et al 2007;Kim et al 2008) the landholder survey was found to be a useful tool for identifying the attitudes, impediments and drivers of management adoption amongst landholders (Bewsell et al 2007). In this case, the survey provided an understanding of the broad impediments to and perceived benefits of adoption of water quality management.…”
Section: Discussionsupporting
confidence: 67%
“…However, there are many factors influencing the adoption of on-farm water quality management measures by landholders (Rhodes et al 2002;MacGregor and Warren 2006;Kim et al 2008;Prokopy et al 2008;Greiner et al 2009). The relative significance of these impediments can vary both between catchments and between individual farmers within catchments (Pannell et al 2006;Bewsell et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…• Higher revenue (Kim et al, 2008) • Higher productivity (Kim et al, 2008;Hiwassee River Watershed Coalition Inc., 2008;Vendramini and Sollenberger, 2010;Eaton et al, 2011) • Lower profitability at similar stocking rates • Improved long-term profitability (Murphy, 1998;Undersander et al, 2002) Higher stocking rate (Eaton et al, 2011) • Significant initial investment cost and increased management costs (Ball et al, 1999). • High start-up costs for fencing, water, and feed bunks (Hiwassee River Watershed…”
Section: No Tillagementioning
confidence: 97%
“…Similarly, Kim et al (2008) found that cattle producers were reluctant to answer contingent valuation questions. …”
Section: Responses To Contingent Valuationmentioning
confidence: 99%